The Relation Between Nusantara Islam and Islamic Education in Contemporary Indonesia - Moch. Tolchah (Al-Ulum, 2016)
Relation between â€˜Nusantara Islamâ€™ and Islamic education in contemporary Indonesia is a pivotal issue. It is because of many fundamental reasons, such as, historical, social, political, cultural, religious and educational perspectives. In this context, this article focuses on the relationship and the contribution of Nusantara Islam in Indonesian Islamic educational context from time to time in all aspects. The research in this paper is qualitative with descriptive analytical approach and documentary method. The general objective of this study is to find out what and how the history of Nusantara Islam in the country? What and how the history of Islamic education in Indonesia? How is the relationship between Nusantara Islam and Islamic education in contemporary Indonesia? The results showed that, first and foremost, is the history of Nusantara Islam is a portrait of a very complex history, which extends from the Aceh to Papua and elsewhere in Indonesia. Second, the history of Indonesian Islamic education is the discussion about institution, content of materials and objectives of Islamic-based education from time to time. Third, the relationship between Nusantara Islam and Islamic education in contemporary Indonesia has a strong â€œbondâ€ with each other. Ultimately, the relationship is so closely linked to the development and progress of the nationhood.